(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2020)
In this investigation, a methodology based on Social Constructivism is proposed to favor the assimilation of theorems through the process of Problem Solving in the students of the Higher Technical University level of the Autonomous University of Guerrero, Mexico. The theoretical-qualitative validation of the methodology was carried out by consulting experts who contributed to systematize the link between the theory and the methodological elements and its implication in the design of specific activities for the treatment of the theorem of variable change.